Курганы в ландшафте Северного Причерноморья. I. Предгорный Крым - Смекалова, Т.Н. (Боспорские исследования, 2009)
The article is devoted to the problem of appropriateness of territorial and chronological spreading of tumuli in the steppes of the north Pontic area. The main scientific method revealed tumuli on detailed maps, on a half verst scale military map of the close of the 19th century. Natural peculiarities of steppes determining way of life and occupation of the peoples who lived in steppes are observed. Common questions concerning the reasons of creating of tumuli, the process of building them, natural materials that were used, dimensions of barrow mounds, labour resources spent for constructing are touched upon.